Two new species of Euconnus (Rhomboconnus) in Peru and Bolivia (Coleoptera, Staphylinidae, Scydmaeninae) - Jałoszyński, Paweł (Zootaxa, 2018)
To date, the subgenus Rhomboconnus Franz of Euconnus Thomson was represented by ten species known to occur in Venezuela, Panama and Ecuador. For the first time Rhomboconnus is reported to occur in Peru and Bolivia, and two new species are described: Euconnus wari sp. n. (Peru) and E. inkachakanus sp. n. (Bolivia). The latter species is the largest representative of Rhomboconnus, with body length exceeding 3 mm.